Implementation of Low Cost Automatic Retrieved Side Stand Mechanism to ensure Safety of Two-Wheeler Riders - Sharma, Rahul (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
Automobile takes a great part in the development of a modern world. While automobile is concern two-wheeler plays a very important role because it saves the time of traveler by reaching the target place very faster. We know that carelessness with side stand invite major accidents. So we are making such a mechanism that will automatically retrieve the side stand as soon as motorcycle starts moving. The side stand is used for supporting a parked motorcycle. If the rider may forget to retract the side stands before riding, then the undistracted stand hitting the ground will affect the riders control during the turn or it may lead to a serious accident. Our goal is to make such a mechanism in motorcycles that side stand automatically retrieve itself. This will ensure safety of two-wheeler riders and will help a lot in saving many lives.